CRYPTOCURRENCY, NILAI TUKAR DAN REAL ASSET TERHADAP HARGA SAHAM PADA PERBANKAN INDONESIA YANG TERDAFTAR DI BURSA EFEK INDONESIA - Marganda Saut Parulian Sihombing (2020)
The purpose of this study is to determine and analyze the effect of Cryptocurrency, Exchange Rate and Real Asset on Stock Prices in Indonesian Banks listed on the Indonesia Stock Exchange for the period 2016-2018. This research uses quantitative methods with explanatory research design. The population in this study were all banking companies listed on the Indonesia Stock Exchange, totaling 43 banking companies. Withdrawal of the number of samples using probability sampling method with simple random sampling technique, and based on the Slovin formula, the minimum number of samples is 39 companies. The data analysis technique uses multiple linear regression analysis using the Eviews 7 program. The results of the hypothesis show that cryptocurrency has a positive effect on stock prices. The Rupiah Exchange Rate has a positive effect on Stock Prices. Gold Price has a positive effect on stock prices. For this reason, it is recommended that prospective investors who wish to buy shares first look at the condition of the stock market based on macroeconomic analysis such as cryptocurrency, rupiah exchange rates and world gold prices, because these three factors are proven to affect the ups and downs of stock prices in the banking sector.The results of the hypothesis show that Cryptocurrency has a positive effect on Stock Prices. The Rupiah Exchange Rate has a positive effect on Stock Prices. Gold Price has a positive effect on Stock Prices. For this reason, it is recommended for prospective investors who wish to buy shares in order to first look at the condition of the stock market based on macroeconomic analysis such as cryptocurrency, rupiah exchange rates and world gold prices, because these three factors are proven to affect the ups and downs of stock prices in the banking sector.